American in the Shadows : Harry Dexter White and the Design of the International Monetary Fund - Boughton, James (IMF Working Papers; Working Paper, 2006)
Two economists designed the main features of the charter of the IMF during World War II: John Maynard Keynes and Harry Dexter White. Several of those features are attributable primarily to White, including the adoption of fixed but adjustable exchange rates, the funding of operations with national currencies deposited by member states, extending credits through currency swaps rather than conventional loans, making these credits subject to policy conditions, and encouraging members to retain capital controls as an option for use in difficult circumstances. This study of archival material helps to uncover White's role in this design process.